A method and device for preparing high temperature stable phase change reinforced ceramic fiber composite material
By using multi-step pretreatment, mixing, forming and sintering technical means in the preparation process of ceramic fiber composites, the problem of the residual substances on the surface and preparation parameters of ceramic fibers cannot be accurately adjusted, and the performance and application range of composite materials are significantly improved.
Patent Information
- Application Number
- CN202411685477.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-23
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-11-23
AI Technical Summary
The presence of residual substances on the surface of the existing ceramic fiber composite materials during the preparation process leads to a reduction in the mixing effect, and the temperature, pressure, speed and preparation time cannot be accurately adjusted, resulting in a reduction in material performance and limited application range.
The ceramic fibers are cleaned and dried using pretreatment devices including pickling sinks, alkali sinks, water sinks and hot air dryers. The phase change reinforcement materials are crushed and screened through ball mills and vibrating screens, and are prepared and processed through a mixing mixer, mold and press, sintering furnace, and grinding and polishing machines.
It improves the mixing effect of ceramic fibers and phase change reinforcement materials, enhances the high temperature stability, hardness, wear resistance, impact resistance and service life of composite materials, and expands the application range.
Smart Images

Figure CN119176720B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phase change reinforced ceramic fiber composites, and in particular to a method and device for preparing a high-temperature stable phase change reinforced ceramic fiber composite material. Background Art
[0002] Ceramic fiber is a fibrous lightweight refractory material with the advantages of light weight, high temperature resistance, good thermal stability, low thermal conductivity, low specific heat and resistance to mechanical vibration. Phase change reinforced material is a substance that can absorb and release a large amount of latent heat. Its working principle is to change its physical state within a certain temperature range to absorb or release energy. The phase change reinforced ceramic fiber composite material obtained by compounding the two materials can optimize and improve the material performance.
[0003] The defects of existing ceramic fiber composite materials are:
[0004] 1. Patent document JP2002029846A discloses a method for manufacturing ceramic fiber reinforced ceramic composite materials. However, the above document does not clean the residual substances such as oxides and oil stains on the surface of the ceramic fibers. During the mixing process, the residual substances on the surface of the ceramic fibers are likely to reduce the mixing effect and the performance of the composite materials.
[0005] 2. Patent document JP2013147366A discloses a ceramic fiber reinforced composite material and a method for producing a ceramic fiber reinforced composite material. However, in the above document, the temperature, pressure, rotation speed and preparation time are not accurately adjusted during the preparation process. Therefore, when the temperature, pressure, rotation speed and preparation time do not meet the standards during the preparation process, the effect of the prepared composite material will be reduced.
[0006] 3. Patent document US06248677B1 discloses a ceramic fiber composite material and a composite material preparation process, but the ceramic fiber composite material prepared in the above document has a technical problem of poor effect when facing impact and high temperature transmission;
[0007] 4. Patent document CN102024901B discloses a method for preparing a piezoelectric ceramic fiber composite material. However, the composite material prepared by the additives used in the above document has a relatively simple effect and a technical problem of a small application range. Summary of the invention
[0008] The object of the present invention is to provide a method and device for preparing a high-temperature stable phase-change reinforced ceramic fiber composite material to solve the technical problems raised in the above-mentioned background technology.
[0009] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: a high-temperature stable phase-change reinforced ceramic fiber composite material preparation device, comprising a pretreatment device, a mixing preparation device, a molding device, a sintering device and a post-treatment device, wherein the pretreatment device comprises a ceramic fiber pretreatment device and a phase-change reinforced material pretreatment device, wherein the ceramic fiber pretreatment device is used to pre-treat the ceramic fiber, the phase-change reinforced material pretreatment device is used to pre-treat the phase-change reinforced material, the mixing preparation device is used to mix and stir the pre-treated materials, the molding device is used to mold the mixed materials, the sintering device is used to perform high-temperature sintering on the molded composite material, and the post-treatment device is used to perform post-treatment on the sintered composite material;
[0010] The ceramic fiber pretreatment device includes an acid washing tank, an alkali washing tank, a water washing tank and a hot air dryer. The acid washing tank is used to remove oxides, oil stains and impurities on the surface of the ceramic fiber. The alkali washing tank is used to further clean the ceramic fiber and remove residual acidic substances and impurities. The water washing tank is used to remove residual acid and alkali solutions. The hot air dryer is used to dry the cleaned ceramic fiber. The phase change reinforcement material pretreatment device includes a ball mill, a vibrating screen and a hot air dryer. The ball mill is used to crush the phase change reinforcement material into smaller particles. The vibrating screen is used to screen the crushed material. The hot air dryer is used to dry the phase change reinforcement material.
[0011] The mixing preparation device includes a mixing mixer, the forming device includes a mold and a press, which are used to input the mixed material into the mold, and obtain the forming device by applying pressure to the mold by the press, the sintering device includes a sintering furnace, and the post-processing device includes a grinder and a polisher, which are used to grind and polish the sintered composite material.
[0012] Preferably, the working steps of the method for preparing the high temperature stable phase change reinforced ceramic fiber composite material are as follows:
[0013] Step S1, selecting the required ceramic fiber material and sequentially adding it into the acid washing tank, the alkali washing tank and the water washing tank to remove surface impurities and oil stains, and then inputting the washed ceramic fiber material into the hot air dryer for drying;
[0014] Step S2, selecting the required ceramic fiber material phase change reinforcement material, crushing the material by a ball mill, and then screening out particles with a particle size that meets the standard by a vibrating screen, and drying the particles that meet the standard by a hot air dryer;
[0015] Step S3, mixing the pretreated ceramic fiber and the phase change reinforcement material in a ratio of 1:0.5-2, adding additives, and putting them into a mixing and stirring machine for mixing and stirring;
[0016] Step S4, pouring the composite material mixed and stirred in step S3 into a mold, and pressing and molding it by a press machine and a mold;
[0017] Step S5, placing the formed composite material into a sintering furnace for high-temperature sintering;
[0018] Step S6: grinding and polishing the sintered composite material by a grinder and a polisher to improve its surface quality and performance.
[0019] Preferably, the hot air dryer used in step S1 has a drying temperature of 110° C. to 140° C., a humidity of 25% to 55% saturated steam humidity, and a drying time of 5 h to 7 h.
[0020] Preferably, the mesh size of the vibrating screen in step S2 is 300 meshes, the drying temperature of the hot air dryer is 70° C.-90° C., the humidity is 40%-75% saturated steam humidity, and the drying time is 3h-4.5h.
[0021] Preferably, in step S3, the additives added include a binder, an antioxidant, a pore regulator, a surfactant and a stabilizer;
[0022] The ratios of the binder, antioxidant, pore regulator, surfactant and stabilizer to the ceramic fiber material are: binder 0.02-0.05:1, antioxidant 0.03-0.06:1, pore regulator 0.08-0.13:1, surfactant 0.02-0.04:1 and stabilizer 0.01-0.02:1.
[0023] Preferably, the adhesive is one of epoxy resin or silicate, which is used to enhance the interfacial bonding force between the ceramic fiber and the phase change reinforcement material;
[0024] The antioxidant is one of chromium oxide and manganese oxide, which is used to improve the antioxidant performance of the composite material;
[0025] The pore regulator is one of carbon black or graphite, which is used to control the porosity and pore size distribution in the composite material to adjust the density, thermal conductivity and mechanical properties of the composite material;
[0026] The surfactant is one of fatty acid glyceride or fatty acid sorbitan, which is used to improve the dispersibility and wettability of the ceramic fiber and the phase change reinforcement material during the mixing process;
[0027] The stabilizer is one of lead salt, metal soap or organic tin, which is used to stabilize the phase change temperature and phase change latent heat of the phase change material.
[0028] Preferably, in step S3, the mixing and stirring machine operates at a speed of 430 r / min-650 r / min, a temperature of 50° C.-80° C., and a time of 1.5 h-3 h.
[0029] Preferably, the pressure of the pressing molding in step S4 is 5MPa-10MPa.
[0030] Preferably, in step S5, the sintering temperature of the sintering furnace is 650° C.-800° C., and the sintering time is 7 h-12 h.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The present invention is provided with a pretreatment device, a mixing preparation device, a molding device, a sintering device and a post-treatment device. During the preparation, the acid washing tank, the alkaline washing tank and the water washing tank in the pretreatment device are provided to sequentially remove the oxides, oil stains, residual acidic substances and residual acid and alkali solutions on the surface of the ceramic fiber, and the particles with a size less than 300 mesh are screened out by the setting of the vibrating screen, thereby improving the mixing effect of the ceramic fiber and the phase change reinforcement material, and improving the high temperature stability, hardness, wear resistance, impact resistance and service life of the obtained composite material;
[0033] 2. The present invention is conducive to obtaining a composite material with higher high temperature stability, stronger hardness, better wear resistance, stronger impact resistance and longer service life by accurately controlling the temperature, pressure, rotation speed and preparation time of each device during the preparation process;
[0034] 3. The present invention uses the ceramic fiber itself to have high strength and hardness, and can improve the toughness of the composite material by adding a phase change reinforcement material. By adjusting the mixing ratio of the ceramic fiber and the phase change reinforcement material according to the needs of the desired composite material, the composite material can have a better use effect when subjected to impact or high temperature transmission;
[0035] 4. The present invention can improve the interface bonding force, antioxidant performance, mechanical properties, dispersibility and phase change latent heat performance between the reinforced ceramic fiber and the phase change reinforced material by setting up adhesives, antioxidants, pore regulators, surfactants and stabilizers, thereby improving the high temperature stability, hardness, wear resistance, impact resistance, service life and scope of use of the obtained composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a schematic diagram of the working process of each device of the present invention;
[0037] Figure 2 It is a schematic diagram of the work flow structure of the present invention. DETAILED DESCRIPTION
[0038] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1: Please refer to Figure 1 , an embodiment provided by the present invention: a high-temperature stable phase-change reinforced ceramic fiber composite material preparation device, including a pretreatment device, a mixing preparation device, a molding device, a sintering device and a post-treatment device, the pretreatment device including a ceramic fiber pretreatment device and a phase-change reinforced material pretreatment device, the ceramic fiber pretreatment device is used to pre-treat the ceramic fiber, the phase-change reinforced material pretreatment device is used to pre-treat the phase-change reinforced material, the mixing preparation device is used to mix and stir the pre-treated materials, the molding device is used to mold the mixed materials, the sintering device is used to perform high-temperature sintering on the molded composite material, and the post-treatment device is used to post-treat the sintered composite material;
[0040] The ceramic fiber pretreatment device includes an acid washing tank, an alkali washing tank, a water washing tank and a hot air dryer. The acid washing tank is used to remove oxides, oil stains and impurities on the surface of the ceramic fiber. The alkali washing tank is used to further clean the ceramic fiber and remove residual acidic substances and impurities. The water washing tank is used to remove residual acid and alkali solutions. The hot air dryer is used to dry the cleaned ceramic fiber. The phase change reinforcement material pretreatment device includes a ball mill, a vibrating screen and a hot air dryer. The ball mill is used to crush the phase change reinforcement material into smaller particles. The vibrating screen is used to screen the crushed material. The hot air dryer is used to dry the phase change reinforcement material.
[0041] The mixing and preparing device includes a mixing and stirring machine, the forming device includes a mold and a press, which are used to input the mixed material into the mold, and the mold is pressed by the press to obtain the forming device, the sintering device includes a sintering furnace, and the post-processing device includes a grinder and a polisher, which are used to grind and polish the sintered composite material;
[0042] Furthermore, the ceramic fibers can be cleaned by the ceramic fiber pretreatment device, the phase change reinforcement material pretreatment device can crush the phase change reinforcement material into particles of the required particle size, and the use of a mixing mixer is beneficial to improving the mixing effect of the ceramic fibers and the phase change reinforcement material. The molded composite material can be obtained by the setting of the mold and the press, and the physical and chemical properties of the composite material can be improved by the sintering furnace. Finally, the sintered collection is ground and polished by the grinder and the polisher to improve the surface quality of the composite material.
[0043] Example 2: Please refer to Figure 2, an embodiment provided by the present invention: the working steps of the method for preparing the high temperature stable phase change reinforced ceramic fiber composite material are as follows:
[0044] Step S1, selecting the required ceramic fiber material and sequentially adding it into the acid washing tank, the alkali washing tank and the water washing tank to remove surface impurities and oil stains, and then inputting the washed ceramic fiber material into the hot air dryer for drying;
[0045] Step S2, selecting the required ceramic fiber material phase change reinforcement material, crushing the material by a ball mill, and then screening out particles with a particle size that meets the standard by a vibrating screen, and drying the particles that meet the standard by a hot air dryer;
[0046] Step S3, mixing the pretreated ceramic fiber and the phase change reinforcement material in a ratio of 1:1, adding additives, and putting them into a mixing and stirring machine for mixing and stirring;
[0047] Step S4, pouring the composite material mixed and stirred in step S3 into a mold, and pressing and molding it by a press machine and a mold;
[0048] Step S5, placing the formed composite material into a sintering furnace for high-temperature sintering;
[0049] Step S6, grinding and polishing the sintered composite material by a grinder and a polisher to improve its surface quality and performance;
[0050] The hot air dryer used in step S1 has a drying temperature of 125°C, a humidity of 40% saturated steam humidity, and a drying time of 6 hours;
[0051] The mesh number of the vibrating screen in step S2 is 300 meshes, the drying temperature of the hot air dryer is 80° C., the humidity is 55% saturated steam humidity, and the drying time is 4 hours;
[0052] In step S3, the additives added include a binder, an antioxidant, a pore regulator, a surfactant and a stabilizer;
[0053] The ratios of the binder, antioxidant, pore regulator, surfactant and stabilizer to the ceramic fiber material are: binder 0.04:1, antioxidant 0.04:1, pore regulator 0.1:1, surfactant 0.03:1 and stabilizer 0.015:1;
[0054] The adhesive is one of epoxy resin or silicate, which is used to enhance the interface bonding force between the ceramic fiber and the phase change reinforcement material;
[0055] The antioxidant is one of chromium oxide and manganese oxide, which is used to improve the antioxidant performance of the composite material;
[0056] The pore regulator is one of carbon black or graphite, which is used to control the porosity and pore size distribution in the composite material to adjust the density, thermal conductivity and mechanical properties of the composite material;
[0057] The surfactant is one of fatty acid glyceride or fatty acid sorbitan, which is used to improve the dispersibility and wettability of the ceramic fiber and the phase change reinforcement material during the mixing process;
[0058] The stabilizer is one of lead salt, metal soap or organic tin, which is used to stabilize the phase change temperature and phase change latent heat of the phase change material;
[0059] In step S3, the mixing and stirring machine operates at a speed of 500 r / min, a temperature of 65° C., and a time of 2 h;
[0060] The pressure of the pressing molding in step S4 is 8 MPa;
[0061] In step S5, the sintering temperature of the sintering furnace is 750° C., and the sintering time is 10 hours.
[0062] Example 3: Please refer to Figure 2 , an embodiment provided by the present invention: the working steps of the method for preparing the high temperature stable phase change reinforced ceramic fiber composite material are as follows:
[0063] Step S1, selecting the required ceramic fiber material and sequentially adding it into the acid washing tank, the alkali washing tank and the water washing tank to remove surface impurities and oil stains, and then inputting the washed ceramic fiber material into the hot air dryer for drying;
[0064] Step S2, selecting the required ceramic fiber material phase change reinforcement material, crushing the material by a ball mill, and then screening out particles with a particle size that meets the standard by a vibrating screen, and drying the particles that meet the standard by a hot air dryer;
[0065] Step S3, mixing the pretreated ceramic fiber and the phase change reinforcement material in a ratio of 1:1, adding additives, and putting them into a mixing and stirring machine for mixing and stirring;
[0066] Step S4, pouring the composite material mixed and stirred in step S3 into a mold, and pressing and molding it by a press machine and a mold;
[0067] Step S5, placing the formed composite material into a sintering furnace for high-temperature sintering;
[0068] Step S6, grinding and polishing the sintered composite material by a grinder and a polisher to improve its surface quality and performance;
[0069] The hot air dryer used in step S1 has a drying temperature of 110° C., a humidity of 55% saturated steam humidity, and a drying time of 5 h;
[0070] The mesh number of the vibrating screen in step S2 is 300 meshes, the drying temperature of the hot air dryer is 70° C., the humidity is 65% saturated steam humidity, and the drying time is 4.5 h;
[0071] In step S3, the additives added include a binder, an antioxidant, a pore regulator, a surfactant and a stabilizer;
[0072] The ratios of the binder, antioxidant, pore regulator, surfactant and stabilizer to the ceramic fiber material are: binder 0.02:1, antioxidant 0.03:1, pore regulator 0.13:1, surfactant 0.04:1 and stabilizer 0.01:1;
[0073] The adhesive is one of epoxy resin or silicate, which is used to enhance the interface bonding force between the ceramic fiber and the phase change reinforcement material;
[0074] The antioxidant is one of chromium oxide and manganese oxide, which is used to improve the antioxidant performance of the composite material;
[0075] The pore regulator is one of carbon black or graphite, which is used to control the porosity and pore size distribution in the composite material to adjust the density, thermal conductivity and mechanical properties of the composite material;
[0076] The surfactant is one of fatty acid glyceride or fatty acid sorbitan, which is used to improve the dispersibility and wettability of the ceramic fiber and the phase change reinforcement material during the mixing process;
[0077] The stabilizer is one of lead salt, metal soap or organic tin, which is used to stabilize the phase change temperature and phase change latent heat of the phase change material;
[0078] In step S3, the mixing and stirring machine operates at a speed of 430 r / min, a temperature of 80° C., and a time of 1.5 h;
[0079] The pressure of the pressing molding in step S4 is 5 MPa;
[0080] In step S5, the sintering temperature of the sintering furnace is 650° C., and the sintering time is 12 hours.
[0081] Example 4: Please refer to Figure 2 , an embodiment provided by the present invention: the working steps of the method for preparing the high temperature stable phase change reinforced ceramic fiber composite material are as follows:
[0082] Step S1, selecting the required ceramic fiber material and sequentially adding it into the acid washing tank, the alkali washing tank and the water washing tank to remove surface impurities and oil stains, and then inputting the washed ceramic fiber material into the hot air dryer for drying;
[0083] Step S2, selecting the required ceramic fiber material phase change reinforcement material, crushing the material by a ball mill, and then screening out particles with a particle size that meets the standard by a vibrating screen, and drying the particles that meet the standard by a hot air dryer;
[0084] Step S3, mixing the pretreated ceramic fiber and the phase change reinforcement material in a ratio of 1:1, adding additives, and putting them into a mixing and stirring machine for mixing and stirring;
[0085] Step S4, pouring the composite material mixed and stirred in step S3 into a mold, and pressing and molding it by a press machine and a mold;
[0086] Step S5, placing the formed composite material into a sintering furnace for high-temperature sintering;
[0087] Step S6, grinding and polishing the sintered composite material by a grinder and a polisher to improve its surface quality and performance;
[0088] The hot air dryer used in step S1 has a drying temperature of 140°C, a humidity of 55% saturated steam humidity, and a drying time of 7 hours;
[0089] The mesh number of the vibrating screen in step S2 is 300 meshes, the drying temperature of the hot air dryer is 90° C., the humidity is 75% saturated steam humidity, and the drying time is 3 hours;
[0090] In step S3, the additives added include a binder, an antioxidant, a pore regulator, a surfactant and a stabilizer;
[0091] The ratios of the binder, antioxidant, pore regulator, surfactant and stabilizer to the ceramic fiber material are: binder 0.05:1, antioxidant 0.03:1, pore regulator 0.13:1, surfactant 0.04:1 and stabilizer 0.02:1;
[0092] The adhesive is one of epoxy resin or silicate, which is used to enhance the interface bonding force between the ceramic fiber and the phase change reinforcement material;
[0093] The antioxidant is one of chromium oxide and manganese oxide, which is used to improve the antioxidant performance of the composite material;
[0094] The pore regulator is one of carbon black or graphite, which is used to control the porosity and pore size distribution in the composite material to adjust the density, thermal conductivity and mechanical properties of the composite material;
[0095] The surfactant is one of fatty acid glyceride or fatty acid sorbitan, which is used to improve the dispersibility and wettability of the ceramic fiber and the phase change reinforcement material during the mixing process;
[0096] The stabilizer is one of lead salt, metal soap or organic tin, which is used to stabilize the phase change temperature and phase change latent heat of the phase change material;
[0097] In step S3, the mixing and stirring machine operates at a speed of 500 r / min, a temperature of 60° C., and a time of 3 h;
[0098] The pressure of the pressing molding in step S4 is 10 MPa;
[0099] In step S5, the sintering temperature of the sintering furnace is 800° C. and the sintering time is 7 hours.
[0100] Example 5: Please refer to Figure 2 , an embodiment provided by the present invention: the working steps of the method for preparing the high temperature stable phase change reinforced ceramic fiber composite material are as follows:
[0101] Step S1, selecting the required ceramic fiber material and sequentially adding it into the acid washing tank, the alkali washing tank and the water washing tank to remove surface impurities and oil stains, and then inputting the washed ceramic fiber material into the hot air dryer for drying;
[0102] Step S2, selecting the required ceramic fiber material phase change reinforcement material, crushing the material by a ball mill, and then screening out particles with a particle size that meets the standard by a vibrating screen, and drying the particles that meet the standard by a hot air dryer;
[0103] Step S3, mixing the pretreated ceramic fiber and the phase change reinforcement material in a ratio of 1:1, adding additives, and putting them into a mixing and stirring machine for mixing and stirring;
[0104] Step S4, pouring the composite material mixed and stirred in step S3 into a mold, and pressing and molding it by a press machine and a mold;
[0105] Step S5, placing the formed composite material into a sintering furnace for high-temperature sintering;
[0106] Step S6, grinding and polishing the sintered composite material by a grinder and a polisher to improve its surface quality and performance;
[0107] The hot air dryer used in step S1 has a drying temperature of 110°C, a humidity of 25% saturated steam humidity, and a drying time of 5.5 h;
[0108] The mesh number of the vibrating screen in step S2 is 300 meshes, the drying temperature of the hot air dryer is 80° C., the humidity is 40% saturated steam humidity, and the drying time is 4.5 h;
[0109] In step S3, the additives added include a binder, an antioxidant, a pore regulator, a surfactant and a stabilizer;
[0110] The ratios of the binder, antioxidant, pore regulator, surfactant and stabilizer to the ceramic fiber material are: binder 0.05:1, antioxidant 0.03:1, pore regulator 0.13:1, surfactant 0.02:1 and stabilizer 0.02:1;
[0111] The adhesive is one of epoxy resin or silicate, which is used to enhance the interface bonding force between the ceramic fiber and the phase change reinforcement material;
[0112] The antioxidant is one of chromium oxide and manganese oxide, which is used to improve the antioxidant performance of the composite material;
[0113] The pore regulator is one of carbon black or graphite, which is used to control the porosity and pore size distribution in the composite material to adjust the density, thermal conductivity and mechanical properties of the composite material;
[0114] The surfactant is one of fatty acid glyceride or fatty acid sorbitan, which is used to improve the dispersibility and wettability of the ceramic fiber and the phase change reinforcement material during the mixing process;
[0115] The stabilizer is one of lead salt, metal soap or organic tin, which is used to stabilize the phase change temperature and phase change latent heat of the phase change material;
[0116] In step S3, the mixing and stirring machine operates at a speed of 650 r / min, a temperature of 60° C., and a time of 1.9 h;
[0117] The pressure of the pressing molding in step S4 is 9 MPa;
[0118] In step S5, the sintering temperature of the sintering furnace is 800° C., and the sintering time is 9 hours.
[0119] Example 6: Please refer to Figure 2 An embodiment provided by the present invention: The specific implementation method is the same as that of Example 2, except that: Step S3, the pretreated ceramic fiber and the phase change reinforcement material are mixed in a ratio of 1:0.5, and additives are added, and the mixture is put into a mixing mixer for mixing and stirring.
[0120] Example 7: Please refer to Figure 2An embodiment provided by the present invention: The specific implementation method is the same as that of Example 2, except that: Step S3, the pretreated ceramic fiber and the phase change reinforcement material are mixed in a ratio of 1:2, and additives are added, and the mixture is put into a mixing mixer for mixing and stirring.
[0121] Comparative Example 1: The working steps of the method for preparing the high temperature stable phase change reinforced ceramic fiber composite material are as follows:
[0122] Step S1, selecting the required ceramic fiber material and sequentially adding it into the acid washing tank, the alkali washing tank and the water washing tank to remove surface impurities and oil stains, and then inputting the washed ceramic fiber material into the hot air dryer for drying;
[0123] Step S2, selecting the required ceramic fiber material phase change reinforcement material, crushing the material by a ball mill, and then screening out particles with a particle size that meets the standard by a vibrating screen, and drying the particles that meet the standard by a hot air dryer;
[0124] Step S3, mixing the pretreated ceramic fiber and the phase change reinforcement material in a ratio of 1:1, adding additives, and putting them into a mixing and stirring machine for mixing and stirring;
[0125] Step S4, pouring the composite material mixed and stirred in step S3 into a mold, and pressing and molding it by a press machine and a mold;
[0126] Step S5, placing the formed composite material into a sintering furnace for high-temperature sintering;
[0127] Step S6, grinding and polishing the sintered composite material by a grinder and a polisher to improve its surface quality and performance;
[0128] The hot air dryer used in step S1 has a drying temperature of 100°C, a humidity of 20% saturated steam humidity, and a drying time of 4 hours;
[0129] The mesh number of the vibrating screen in step S2 is 300 meshes, the drying temperature of the hot air dryer is 60° C., the humidity is 30% saturated steam humidity, and the drying time is 2.5 h;
[0130] In step S3, the additives added include a binder, an antioxidant, a pore regulator, a surfactant and a stabilizer;
[0131] The ratios of the binder, antioxidant, pore regulator, surfactant and stabilizer to the ceramic fiber material are: binder 0.01:1, antioxidant 0.02:1, pore regulator 0.06:1, surfactant 0.01:1 and stabilizer 0.005:1;
[0132] The adhesive is one of epoxy resin or silicate, which is used to enhance the interface bonding force between the ceramic fiber and the phase change reinforcement material;
[0133] The antioxidant is one of chromium oxide and manganese oxide, which is used to improve the antioxidant performance of the composite material;
[0134] The pore regulator is one of carbon black or graphite, which is used to control the porosity and pore size distribution in the composite material to adjust the density, thermal conductivity and mechanical properties of the composite material;
[0135] The surfactant is one of fatty acid glyceride or fatty acid sorbitan, which is used to improve the dispersibility and wettability of the ceramic fiber and the phase change reinforcement material during the mixing process;
[0136] The stabilizer is one of lead salt, metal soap or organic tin, which is used to stabilize the phase change temperature and phase change latent heat of the phase change material;
[0137] In step S3, the mixing and stirring machine operates at a speed of 400 r / min, a temperature of 40° C., and a time of 1.2 h;
[0138] The pressure of the pressing molding in step S4 is 4 MPa;
[0139] In step S5, the sintering temperature of the sintering furnace is 600° C., and the sintering time is 6 hours.
[0140] Comparative Example 2: The specific implementation method is the same as Example 2, except that: in step S3, the additives added are antioxidants, surfactants and stabilizers.
[0141] Comparative Example 3: The specific implementation method is the same as Example 2, except that: Step S1, the required ceramic fiber material is selected and washed only in a water washing tank, and after washing, the ceramic fiber material is input into a hot air dryer for drying.
[0142] Comparative Example 4: The specific implementation method is the same as Example 2, except that: Step S2, selecting the required ceramic fiber material phase change reinforcement material, crushing the material by a ball mill, and drying the crushed particles by a hot air dryer.
[0143] Comparative Example 5: A phase change reinforced ceramic fiber composite material purchased on the market was used.
[0144] Performance Test:
[0145] Test 1: High temperature stability test: The composite materials prepared in Examples 2-7 and Comparative Examples 1-5 were placed in an environment at 200° C., and the initial temperature of the composite materials and the temperature after being placed in the environment at 200° C. for 30 minutes were checked respectively.
[0146] Test 2: Hardness and wear resistance test: The composite materials prepared in Examples 2-7 and Comparative Examples 1-5 were placed on a workbench. When testing the hardness, a Vickers hardness tester was used. A certain pressure was applied to the surface of the material through the pressure device of the hardness tester. The marks produced on the surface of the material were observed, and the diameter of the marks was measured using a microscope or a magnifying glass to calculate the Vickers hardness value of the material.
[0147] During the wear resistance test, a friction tester is used to make the composite material to be tested move relative to the friction body. The wear resistance of the material is evaluated by measuring the wear amount of the sample. The wear resistance performance is divided into: excellent, good, medium and poor.
[0148] Test 3: Impact resistance test: The composite materials prepared in Examples 2-7 and Comparative Examples 1-5 were placed on a test bench and subjected to a falling ball impact test. A sphere of a certain mass was freely dropped from a certain height to impact the surface of the composite material. The impact resistance of the sample was evaluated by assessing whether cracking or damage occurred during the impact process.
[0149] Test 4: After the composite materials prepared in Examples 2-7 and Comparative Examples 1-5 were placed in a room temperature environment for 90 days, the high temperature stability, hardness, wear resistance and impact resistance of the composite materials were tested in turn.
[0150] Table 1 Test results of performance test 1:
[0151]
[0152] Comparing the initial temperature and the temperature after 30 minutes, the temperature after 30 minutes is close to or reaches 200°C, which means that the composite material has good thermal stability in an environment of 200°C;
[0153] If the temperature is much lower than 200°C, it may indicate that the composite material has poor heat conduction or large heat loss problems;
[0154] Temperatures above 200°C may indicate that some thermal reaction or phase change occurred in the composite material during heating.
[0155] Table 2 Test results of performance test 2:
[0156]
[0157] Table 3 Test results of performance test 3:
[0158]
[0159] Table 4 Test results of performance test 4:
[0160] ;
[0161] Further, it can be seen from the data obtained in Tables 1, 2, 3 and 4 above that by setting the pretreatment device, the mixing preparation device, the molding device, the sintering device and the post-treatment device, during the preparation, the acid washing tank, the alkaline washing tank and the water washing tank in the pretreatment device are set to remove the oxides, oil stains, residual acidic substances and residual acid and alkali solutions on the surface of the ceramic fiber in turn, and the particles less than 300 mesh are screened out by the setting of the vibrating screen, thereby improving the mixing effect of the ceramic fiber and the phase change reinforcement material, and improving the high temperature stability, hardness, wear resistance, impact resistance and service life of the obtained composite material;
[0162] By precisely controlling the temperature, pressure, rotation speed and preparation time of each device during the preparation process, it is beneficial to obtain composite materials with higher high temperature stability, stronger hardness, better wear resistance, stronger impact resistance and longer service life;
[0163] Ceramic fiber itself has high strength and hardness, and the toughness of the composite material can be improved by adding phase change reinforcement material. By adjusting the mixing ratio of ceramic fiber and phase change reinforcement material according to the needs of the required composite material, the composite material can have a better use effect when subjected to impact or high temperature transmission;
[0164] By setting up adhesives, antioxidants, pore regulators, surfactants and stabilizers, the interface bonding strength, antioxidant properties, mechanical properties, dispersibility and phase change latent heat properties between the reinforced ceramic fibers and the phase change reinforced materials can be improved respectively, thereby improving the high temperature stability, hardness, wear resistance, impact resistance and service life of the obtained composite materials.
[0165] Working principle: through the setting of pretreatment device, mixing preparation device, molding device, sintering device and post-treatment device, during the preparation, the acid washing tank, alkali washing tank and water washing tank in the pretreatment device are set to remove the oxides, oil stains, residual acidic substances and residual acid and alkali solutions on the surface of the ceramic fiber in turn, and the particles less than 300 mesh are screened out through the setting of the vibrating screen, so as to improve the mixing effect of ceramic fiber and phase change reinforcement material, improve the high temperature stability, hardness, wear resistance, impact resistance and service life of the composite material, and accurately control the temperature, pressure, rotation speed and preparation time of each equipment in the preparation process, which is conducive to obtaining higher high temperature stability, stronger hardness and durability. A composite material with better abrasion resistance, stronger impact resistance and longer service life. The phase change reinforced ceramic fiber composite material obtained by using a pretreatment device, a mixing preparation device, a molding device, a sintering device and a post-treatment device has better high-temperature stability, hardness, wear resistance, impact resistance and service life than the phase change reinforced ceramic fiber composite materials purchased on the market. Through the setting of adhesives, antioxidants, pore regulators, surfactants and stabilizers, the interface bonding force, antioxidant properties, mechanical properties, dispersibility and phase change latent heat properties between the reinforced ceramic fibers and the phase change reinforced materials can be improved respectively, thereby improving the high-temperature stability, hardness, wear resistance, impact resistance and service life of the obtained composite material.
[0166] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a high temperature stable phase change reinforced ceramic fiber composite material, characterized in that: Here are the steps: Step S1, selecting the required ceramic fiber material and sequentially adding it into the acid washing tank, the alkali washing tank and the water washing tank to remove surface impurities and oil stains, and then inputting the washed ceramic fiber material into the hot air dryer for drying; Step S2, selecting the required ceramic fiber material phase change reinforcement material, crushing the material by a ball mill, and then screening out particles with a particle size less than 300 mesh by a vibrating screen, and drying the particles that meet the standards by a hot air dryer; Step S3, mixing the pretreated ceramic fiber and the phase change reinforcement material in a ratio of 1:0.5-2, adding additives, and putting them into a mixing and stirring machine for mixing and stirring; Step S4, pouring the composite material mixed and stirred in step S3 into a mold, and pressing and molding it by a press machine and a mold; Step S5, placing the formed composite material into a sintering furnace for high-temperature sintering; Step S6, grinding and polishing the sintered composite material by a grinder and a polisher to improve its surface quality and performance; In step S3, the additives added include a binder, an antioxidant, a pore regulator, a surfactant and a stabilizer; The ratios of the adhesive, antioxidant, pore regulator, surfactant and stabilizer to the ceramic fiber material are: 0.02-0.05:1, 0.03-0.06:1, 0.08-0.13:1, 0.02-0.04:1, 0.01-0.02:1 respectively; The adhesive is one of epoxy resin or silicate, the antioxidant is one of chromium oxide or manganese oxide, the pore regulator is one of carbon black or graphite, the surfactant is one of fatty acid glyceride or fatty acid sorbitan, and the stabilizer is one of lead salt, metal soap or organic tin.
2. The method for preparing a high temperature stable phase change reinforced ceramic fiber composite material according to claim 1, characterized in that: The hot air dryer used in step S1 has a drying temperature of 110° C. to 140° C., a humidity of 25% to 55% saturated steam humidity, and a drying time of 5 h to 7 h.
3. The method for preparing a high temperature stable phase change reinforced ceramic fiber composite material according to claim 1, characterized in that: The mesh number of the vibrating screen in step S2 is 300 meshes, the drying temperature of the hot air dryer is 70° C.-90° C., the humidity is 40%-75% saturated steam humidity, and the drying time is 3h-4.5h.
4. The method for preparing a high temperature stable phase change reinforced ceramic fiber composite material according to claim 1, characterized in that: In step S3, the mixing and stirring machine operates at a speed of 430 r / min-650 r / min, a temperature of 50° C.-80° C., and a time of 1.5 h-3 h.
5. The method for preparing a high temperature stable phase change reinforced ceramic fiber composite material according to claim 1, characterized in that: The pressure of the pressing molding in step S4 is 5MPa-10MPa.
6. The method for preparing a high temperature stable phase change reinforced ceramic fiber composite material according to claim 1, characterized in that: In the step S5, the sintering temperature of the sintering furnace is 650° C.-800° C., and the sintering time is 7 h-12 h.
Citation Information
Patent Citations
Preparation method of piezoelectric ceramic fiber composite material
CN102024901B
Biaxial-oriented blow-molded resin bottle body and manufacture thereof
JP1988000041A
Easy-open can cover, cut end edge of which can be protected
JP1988000052A
Packaging bag
JP1988000063A
Method for manufacturing ceramic fiber reinforced ceramic composite material
JP2002029846A